Relating Chain Conformation to the Density of States and Charge Transport in Conjugated Polymers: The Role of the β-phase in Poly(9,9-dioctylfluorene) - Shi,X; Nádady,V; Perevedentsev,A; Frost,J; Wang,X; von,Hauff E; Mackenzie,R; Nelson,J (Physical Review X, 2019)
Charge transport in π-conjugated polymers is characterised by a strong degree of disorder in both the energy of conjugated segments and the electronic coupling between adjacent sites. This disorder arises from variations in the structure and conformation of molecular units, as well as the weak inter-molecular binding interactions. Although disorder in molecular conformation can be expected to influence the density of states (DoS) distribution, and hence optoelectronic properties of the material, until now, there has been no direct study of the relationship between a distinct conformational defect and the charge transport properties of a conjugated polymer. Here, we investigate the impact of introducing an extended, planarised chain geometry, known as the ‘β-phase’, on hole transport through otherwise amorphous films of poly(9,9-dioctylfluorene) (PFO). We show that whilst β-phase introduces a striking ~hundredfold drop in time-of-flight (ToF) hole mobility (μh) at room temperature, it reduces the steady-state μh measured from hole-only devices by a factor of less than ~5. In order to reconcile these observations, we combine high-dynamic-range ToF photocurrent spectroscopy and energy-resolved electrochemical impedance spectroscopy to extract the hole DoS of the conjugated polymer. Both methods show that the effect of the β-phase content is to introduce a sharp sub-bandgap feature into the DoS of glassy PFO lying ~0.3 eV above the highest occupied molecular orbital. The observed energy of the conformational trap is consistent with electronic structure calculations using a tight-binding approach. Using the obtained DoS with a drift-diffusion model capable of resolving charge carriers in both time and energy, we show how the seemingly contradictory transport phenomena obtained via the time-resolved, frequency-resolved, and steady-state methods are reconciled. The results highlight the significance of energetic redistribut